The Analyses of Household Income and Dependence on Forest Resources - Sunarto, Sunarto; Setiawan, Avi Budi (Universitas Negeri Semarang, 2019)
The objectives of this study are; (1) to identify the probability of paid work options, (2) to analyze variables affecting the income of the farmers, and (3) to analyze and measure variables that affect the farmers dependence over forest resources. This result indicates that the physical capacity variables affecting the decision for working in the forest. The other influencing reasons in the decision making process to work in the forest is the age of the head of the family, working time which is spent in the forest, the width of the areas, and values of the assets. Generally, the dependence of the farmers over the forest is spatiallyÃ‚Â influenced by the income from non-forest work, the land-owned width, householdÃ¢â‚¬â„¢s head education, number of dependents, and access to the forest, and access to the forest. However, the variable of asset values do not essentially play important role. A new finding is the occurence of the income inequality. It is driven by the inequality of the width of the land as a result of sale and lease of the right to the land in the forest, the conflicts happens through the years, and the disobedience of the farmers over the working period.